Long Non-Coding RNAs: Key Regulators of Gene Expression in Development and Disease - Yashi Dwivedi; Jugal Jaiswal (International Journal of Genetic Modifications and Recombinations, 2025)
Long non-coding RNAs (lncRNAs) are RNA molecules that do not make proteins but are essential for controlling how genes are turned on or off in the body. These molecules help with various biological functions, such as guiding cell growth, shaping development, and influencing the progression of diseases. Recent advancements in genomics and transcriptomics have revealed the vast and complex roles of lncRNAs, with an increasing recognition of their involvement in regulating chromatin structure, transcriptional and post-transcriptional modifications, and the coordination of signaling pathways. LncRNAs exert their effects through diverse mechanisms, such as chromatin remodeling, interaction with transcription factors, serving as scaffolds, and regulating the stability of other RNA species. The aberrant expression or dysfunction of specific lncRNAs has been linked to various diseases, including cancer, neurological disorders, and cardiovascular diseases, making lncRNAs a valuable target for therapeutic interventions. This review focuses on the mechanisms by which lncRNAs regulate gene expression during development and their contribution to disease processes. It also discusses recent advances in understanding how lncRNAs function at the molecular level, highlighting their interactions with chromatin, transcription factors, and other molecular complexes. We also explore how lncRNAs could be used to detect diseases, predict their outcomes, and even serve as possible treatments. Given the emerging understanding of their roles in human biology, lncRNAs represent an exciting and dynamic area of research, offering new insights into the regulation of gene expression and the development of novel therapeutic strategies.
Keywords: Epigenetics; Long non-coding RNAs; RNA scaffolds; chromatin remodeling; gene regulation; transcriptional regulation